The beast within [videorecording (DVD)] - Farrell, Alexander J.; Ellison, Greer Taylor; Harington, Kit, 1986-; Cummings, Ashleigh, 1992-; Cosmo, James; Springall, Caoilinn; Maslin, Miriam Arabella; Basil, Adam (Well Go USA Entertainment, 2024)
After a series of strange events leads her to question her family's isolated life in a remote fortified compound, 10-year-old Willow follows her parents on one of their secret late-night treks deep into the heart of the ancient forest. But upon witnessing her father undergo a terrible transformation, she too becomes ensnared by the terrifying ancestral secret they've tried so desperately to conceal.